Whole‐exome sequencing revealed a nonsense mutation in STKLD1 causing non‐syndromic pre‐axial polydactyly type A affecting only upper limb. Issue 2 (22nd April 2019) - Umair, Muhammad; Bilal, Muhammad; Ali, Raja H.; Alhaddad, Bader; Ahmad, Farooq; Abdullah,; Haack, Tobias B.; Alfadhel, Majid; Ansar, Muhammad; Meitinger, Thomas; Ahmad, Wasim
Abstract: Pre‐axial polydactyly (PPD) is characterized by well‐developed non‐functional 1st digit (thumb) duplication in hands and/or feet. It is mostly inherited in autosomal dominant manner. In the present study, two families of Pakistani origin, demonstrating unilateral PPD type A, have been characterized at clinical and genetic levels. Whole‐exome sequencing (WES) revealed a nonsense mutation (c.84C > A, p.Tyr28*) in the STKLD1, located on chromosome 9q34.2, in affected individuals of both the families. Our findings report the first direct involvement of the STKLD1 in the digit development and highlight the importance of inclusion of this gene for screening individuals presenting non‐syndromic recessive PPD. Abstract : A nonsense variant in the STKLD1 causing pre‐axial polydactyly type A